Regulation of retrotransposition in Arabidopsis. (1st November 2021) - Lee, Seung Cho; Martienssen, Robert A.
Abstract : Plant genomes are largely comprised of retrotransposons which can replicate through 'copy and paste' mechanisms. Long terminal repeat (LTR) retrotransposons are the major class of retrotransposons in plant species, and importantly they broadly affect the expression of nearby genes. Although most LTR retrotransposons are non-functional, active retrotranspositions have been reported in plant species or mutants under normal growth condition and environmental stresses. With the well-defined reference genome and numerous mutant alleles, Arabidopsis studies have significantly expanded our understanding of retrotransposon regulation. Active LTR retrotransposon loci produce virus-like particles to perform reverse transcription, and their complementary DNA can be inserted into new genomic loci. Due to the detrimental consequences of retrotransposition, plants like animals, have developed transcriptional and post-transcriptional silencing mechanisms. Recently several different genome-wide techniques have been developed to understand LTR retrotransposition in Arabidopsis and different plant species. Transposome, methylome, transcriptome, translatome and small RNA sequencing data have revealed how host silencing mechanisms can affect multiple steps of retrotransposition. These recent advances shed light on future mechanistic studies of retrotransposition as well as retrotransposon diversity.